CCEA GCSE learning for life and work - McAleer, Amanda; McAllister, Michaella; McDonnell, Joanne (Dynamic learning, 2017)
Enable students to critically engage with the new content and assessment requirements with this fully updated edition of the market-leading Student's Book for CCEA GCSE Learning for Life and Work - Provides complete coverage of the new content and assessment requirements with support at every stage from experienced teachers and subject experts David McVeigh, Michaella McAllister and Amanda McAleer- Prepares students for assessment with skills-building activities, practice questions and structured guidance on how to approach questions successfully- Helps engage students through accessible diagrams, research activities and a bank of up-to-date case study material- Develops subject knowledge through clear and detailed coverage of the key content structured around the specification